IPower: an energy conservation system for intelligent buildings by wireless sensor networks. (20th February 2009) - Yeh, Lun-Wu; Wang, You-Chiun; Tseng, Yu-Chee
Wireless Sensor Networks (WSNs) provide a convenient way to monitor the physical environment. Exploiting the context-aware capability of WSN to achieve energy conservation in intelligent buildings is an attractive direction. We thus propose an iPower (intelligent and personalised energy conservation system by WSNs) system which combines WSNs and appliance control devices to provide personalised energy conservation services. A WSN is deployed in each room to monitor the usage of electric appliances and to help determine if there are electric appliances that can be turned off for energy conservation. The iPower system is quite intelligent and can adapt to personal need by automatically adjusting electric appliances to satisfy users' requirements. The design and implementation details of iPower are reported in this paper.